UPAYA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) ADECO DALAM PENGEMBANGAN UMKM DI KOTA LANGSA - Yanti, Widya Armayanti Tanjung; Tuti Meutia; Nasrul Kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This research was carried out with the aim of finding out the role of BPR Syariah Adeco in developing MSMEs, how MSMEs develop after obtaining financing and what the mechanism for channeling financing is through Murabahah contracts. This type of research is qualitative research with a descriptive approach. This research uses data sourced from primary data and secondary data. Data collection techniques were carried out using interview, observation and documentation techniques. Data analysis in this research uses steps in the form of data reduction, data presentation and drawing conclusions. The results of the research show that the important role of Adeco Sharia People's Financing Bank (BPRS) in developing MSMEs in Langsa City includes, among other things, providing MSME financing using Murabahah contracts or sale and purchase contracts as well as monitoring the financing and business development of its customers. The development of MSMEs that can be felt after receiving the distribution of funds is increasing sales turnover, increasing income, increasing the number of products, expanding business locations, and increasing workforce. The financing distribution mechanism is through a Murabahah contract which begins with the application stage, follow up, survey, financing analysis stage, approval stage, disbursement stage, monitoring stage up to the repayment stage, in principle in accordance with sharia principles.